Efficacy of right ventricular dysfunction estimated by pulmonary artery pulsatility index in stable phased dilated cardiomyopathy. (25th November 2020) - Kuwayama, T; Morimoto, R; Oishi, H; Kato, H; Kimura, Y; Kazama, S; Shibata, N; Arao, Y; Yamaguchi, S; Hiraiwa, H; Kondo, T; Furusawa, K; et al.
Abstract: Background: Dilated cardiomyopathy (DCM) is characterized by a reduction in left and/or right ventricular myocardial contraction, dilatation of biventricular cavity and major cause of heart failure with high morbidity and mortality rates. Right ventricular dysfunction (RVD) recently have been received attention because of 34% of DCM had RVD and considered as a powerful predictor of impaired prognosis in DCM. Pulmonary Artery Pulsatility index (PAPi) is a novel hemodynamic index shown to predict RVD in advanced heart failure, however, it is unknown that even at early phase, PAPi can reflects latent right myocardial damage and predict long-term prognosis in stable DCM patients. Methods: From April 2000 to March 2018, we enrolled 566 consecutive patients with cardiomyopathy. All patients underwent laboratory measurement, echocardiography, and cardiac catheterization to evaluate their general conditions. After excluded secondary cardiomyopathy, ischemic cardiomyopathy, and valvular heart disease, finally 162 DCM patients were enrolled. All enrolled patients had NYHA I/II/III and NYHA I/II were 150 patients (92.6%). PAPi was calculated as (systolic pulmonary artery pressure – diastolic pulmonary artery pressure (Pulmonary artery pulse pressure: PAPP)) / right atrial pressure. Median followed up for 4.85 years. In this study 149 patients were performed endomyocardial biopsy in order to exclude secondary cardiomyopathies and 95 patients were assessed using Sirius red staining. Myocardial fibrosis in biopsy specimen was assessed using Sirius red staining, and the positive region was quantified as the collagen volume fraction (CVF). Results: The mean age and LV ejection fraction (EF) was 50.9±12.6 years and 30.5±8.3%, respectively. When divided into two groups by median PAPi value [PAPi <3.06 (L-PAP) and PAPi ≥3.06 (H-PAP)], even though there were no significant difference in BNP, pulmonary vascular resistance and right ventricular stroke work index between two groups, the probability of cardiac event-survival was significantly higher in L-PAP than H-PAP by Kaplan-Meier analysis (P=0.012). Furthermore, cox proportional hazard regression analysis revealed that PAPi was independent predictor of cardiac events (hazard ratio: 0.624, P=0.025). In pathological analysis, there was no difference between H-PAPi and L-PAPi in CVF. Conclusion: In the calculation of PAPi, PAPP reflects both RV contractility and left atrial filling pressure and this index considered as RV adaptive response to afterload. The denominator of the PAPP is defined by RA pressure, which serves as a marker of RV preload. Thus, PAPi reflect both preload and afterload of RV at the same time and even though estimated patients at early phase, RVD exists in DCM patients without severe myocardial fibrosis, and PAPi may help stratify DCM and predict cardiac events. Funding Acknowledgement: Type of funding source: None